Metabolic Engineering of Isoflavones: An Updated Overview - Sohn, Soo In; Pandian, Subramani; Oh, Young Ju; Kang, Hyeon Jung; Cho, Woo Suk; Cho, Youn Sung (Frontiers in Plant Science, 2021)
Isoflavones are ecophysiologically active secondary metabolites derived from the phenylpropanoid pathway. They were mostly found in leguminous plants, especially in the pea family. Isoflavones play a key role in plant-environment interactions and acts as phytoalexins also having an array of health benefits to the humans. According to epidemiological studies, high intake of isoflavones-rich diets linked to a lower risk of hormone-related cancers, osteoporosis, menopausal symptoms, and cardiovascular diseases. These characteristics lead to the significant advancement in the studies on genetic and metabolic engineering of isoflavones in plants. As a result, a number of structural and regulatory genes involved in isoflavone biosynthesis in plants have been identified and characterized. Subsequently, they were engineered in various crop plants for the increased production of isoflavones. Further, with the advent of high-throughput technologies, the regulation of isoflavone biosynthesis gaining attention to increase or decrease the level of isoflavones in the crop plants. In the review, we begin with the role of isoflavones in plants, environment and its benefits in human health. Besides, the main theme is to discuss the updated research progress in metabolic engineering of isoflavones in other plants species and regulation of production of isoflavones in soybeans.